Substrate curvature influences cytoskeletal rearrangement and modulates macrophage phenotype - Sovar, Austin; Patrick, Matthew D.; Annamalai, Ramkumar T. (Frontiers in Immunology, 2025)
IntroductionInflammation is a vital immune response, tightly orchestrated through both biochemical and biophysical cues. Dysregulated inflammation contributes to chronic diseases, highlighting the need for novel therapies that modulate immune responses with minimal side effects. While several biochemical pathways of inflammation are well understood, the influence of physical properties such as substrate curvature on immune cell behavior remains underexplored. This study investigates how substrate curvature impacts macrophage cytoskeletal dynamics, gene expression, and immunophenotype through mechanosensitive pathways.MethodsGelatin-based microgels with tunable surface curvatures were fabricated via water-in-oil emulsification and crosslinked with genipin. Microgels were sorted into three size ranges, yielding high (40-50 µm), intermediate (150-250 µm), and low (350-400 µm) curvature profiles. Macrophages were seeded onto these microgels, and cytoskeletal dynamics were examined using confocal microscopy, SEM, and actin-specific staining. Gene expression of pro- and anti-inflammatory markers was quantified using qPCR. The role of actin polymerization was assessed using Latrunculin-A (Lat-A) treatment.ResultsMacrophages adhered effectively to both high- and low-curvature microgels, displaying curvature-dependent morphological changes. Confocal imaging revealed that macrophages on low-curvature microgels exhibited significantly higher F-actin density than those on high-curvature microgels. Correspondingly, qPCR analysis showed upregulation of pro-inflammatory markers (e.g., Tnf, Nos2) in high-curvature conditions, while anti-inflammatory markers (e.g., Arg1) were elevated in low-curvature conditions. Lat-A treatment reduced F-actin density and modulated gene expression patterns, confirming the cytoskeletal regulation of macrophage phenotype.DiscussionThese findings demonstrate that substrate curvature influences macrophage behavior by modulating cytoskeletal dynamics and associated immunophenotypic markers through actin-mediated transcriptional pathways. By controlling curvature, therapeutic biomaterials may direct immune responses, offering a new avenue for treating inflammatory diseases. This mechanobiological approach presents a promising strategy for precision immunomodulation in regenerative medicine.